Dairy Product, Calcium Intake and Lung Cancer Risk: A Systematic Review with Meta-Analysis - Yang, Yang (Sci Rep, 2016)
The effects of dairy products on human health have been studied for years. However, the relationship between dairy products as well as calcium intake and the risk of lung cancer is still inconclusive. A total of 32 studies regarding this association were identified from the PubMed and Web of Science databases through April 1, 2015, including 12 cohort studies and 20 case-control studies. After pooling the results of individual studies, the summary RRs (relative risks) of lung cancer for the highest versus lowest intake were 1.05 (95%CI: 0.84–1.31) and 1.08 (95%CI: 0.80–1.46) for total dairy products and milk, respectively. The results on the consumption of cheese, yogurt and low-fat milk were also negative, and the RRs for total and dietary calcium intakes were 0.99 (95%CI: 0.70–1.38) and 0.85 (95%CI: 0.63–1.13), respectively. After stratifying by potential confounders, the results remained consistent in most subgroup analyses. Our study indicates that intake of dairy products or calcium was not statistically associated with the risk of lung cancer. This negative finding provides a conclusive answer to the disease association issue based on current evidence, and suggests that further efforts should be made to find other nutritional risk factors for lung cancer.